Interpersonal Communication Behaviour of Members of Group Farming Committees in the Adoption of Rice Production Technology - Vipinkumar V P (Department of Agricultural Extension, College of Horticulture, 1994)
A study on the interpersonal communication behaviour efficiency (IPCBE) of the members of rice Group Farming Committee was carried out using 240 respondents selected from the four highest paddy growing districts of Kerala state, namely Palakkad, Thrissur, Ernakulam and Alappuzha. The data were collected with the help of a pretested structured interview schedule by personally interviewing the respondents selected from four highest paddy growing blocks of the above districts. The analysis of the data revealed that, out of fifteen selected personal and socio – psychological characteristics (independent variables) twelve variables were positively and significantly related with IPCBE namely education, socio – economic status, extension orientation, scientific orientation, mass media participation, social participation, cosmopoliteness, knowledge, attitude towards Group Farming, attitude towards other farmers, information source use pattern and farmsize. Of these maximum variation on the dependent variable was caused by four characteristics namely attitude towards other farmers, socio - economic status, extension orientation and attitude towards Group Farming. For measuring the dependent variable IPCBE an index was developed by identifying nine sub – dimensions namely communication skill, competence, empathy, authenticity, interpersonal trust, consistency, positiveness, reciprocity and rationality. The analysis of data revealed that all these dimensions were positively and significantly related with IPCBE, but the maximum variation on IPCBE was caused by mainly four sub – dimensions namely communication skill, empathy, competence and interpersonal trust. The perceived group cohesiveness of the committee members as influenced by IPCBE also was measured and found a positive and significant influence of IPCBE on it. The extent of information flow for adoption of rice production technology through interpersonal means also was measured by listing down the eight critical operations of Group Farming and found that the maximum extent of information flow took place with regard to ‘plant protection’ and the least extent with regard to ‘seed treatment’.